Assessing mineral composition and morpho-physiological properties of de-hulled einkorn wheat during storage at different moisture levels. (September 2019) - Kibar, Hakan
Abstract: In this study were investigated the effects of different moisture levels (4.8, 9.5, 13, 16.7 and 20%, w.b.) during the storage at 10 °C for three months on some mineral compositions and morpho-physiological properties as dimensional (length, width, thickness, arithmetic mean diameter, geometric mean diameter, surface area and volume, sphericity), gravimetric (thousand grain weight, bulk and true densities) and the seed (colour measurement and electrical conductivity) of de-hulled einkorn wheat seeds. Mineral composition of wheat seeds changed with increasing moisture level. In particular, decreases in mineral composition were observed above 16.7% moisture level. Dimensional properties showed increases depending on increased moisture level. It was found that thousand grain weight and true density values increased with increase in moisture level. However, bulk density values were found to decrease with increase in moisture level. The seed colour properties as L*, a*, b*, Chroma, hue angle and Browning index did not change statistically at the end of three months storage with increase at moisture level. The results showed that mineral compositions and functional properties of seeds at moisture level of 9.5% is more suitable than other moisture levels. As a result, high moisture levels during storage can cause degradation of seed quality. Highlights: In the study, both mineral compositions and morpho-physiological properties were affected by moisture level. Especially high moisture levels caused heavy metal level increases in the seeds. Seed color properties were not affected by the increased moisture level. A moisture level of 9.5% was found to be suitable for wheat quality and food safety.